Utilization of AudioVisual Media as a Source of Historical Learning in Distance Learning - Ayuhel Letrik Marian (ICHELSS: International Conference on Humanities, Education, Law, and Social Sciences, 2021)
This study aims to see the effectiveness of audiovisual learning media carried out in distance learning by utilizing the zoom application as a learning medium and the delivery of material in history learning. Researchers used quantitative methods with this type of experiment. The data collection method used was documentation and test. Data analysis at the initial and final stages includes normality test, two-variant similarity test, and two-mean difference test. From the results obtained, it can be seen that the use of audiovisual media in distance learning can be said to be successful, there is an increase in understanding in history learning.